Aplicación para el cálculo y generación de reportes con base en las normas ISO 16283-1:2014, ISO 16283-2:2015, ISO 717-1:2013 e ISO 717-2:2013 (2018)
Using technological tools such as desktop applications on personal computers leads to the optimization of some calculation and result reporting tasks in the field of acoustic measurements. The purpose of this project was to develop a tool to perform these tasks based on the international standards ISO 16283 and ISO 717, parts 1 and 2 (evaluation of acoustic insulation to airborne and impact noise), using Python 2.7 as the main programming language and an agile development methodology known as Extreme Programming. This methodology allows developers to focus on iterative planning and programming of an application and unlike other development methodologies, makes these processes faster by avoiding the making of excessive documentation. Evaluation of this tool was done through statistical tests known as t-tests in order to verify the accuracy of the software results and through usability tests using SUMI surveys with the goal of measuring the user's perception and experience. The results were highly favorable; when comparing the calculations performed by the application with reference results acquired from other programs (CESVA Insulation Studio, Dr Jordan Design AkuLap, Brüel & Kjær QualifierType 7830 and Norsonic NorBuild). In no case the differences were not statistically significant. However, there are some individual differences for some frequency bands, the worst results were obtained for low frequency terms; these results were discussed